2017
DOI: 10.1161/strokeaha.117.018135
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Prehospital Delay of a Stroke Preparedness Campaign

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01881152.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The marginally longer stroke-to-call time depended on larger variability in the cohort-2020, suggesting that stroke awareness campaign might be implemented during the pandemic to reinforce a timely access to emergency services. Citizens' stroke awareness is paramount to guarantee access to treatment, and recent regional campaigns in 2014 [10] and in 2018 (https://salute.regione.emilia-romagna.it/campagne/ ictus-vedo-riconosco-chiamo) might have contributed to early recognition, and encouraged calling emergency services.…”
Section: Discussionmentioning
confidence: 99%
“…The marginally longer stroke-to-call time depended on larger variability in the cohort-2020, suggesting that stroke awareness campaign might be implemented during the pandemic to reinforce a timely access to emergency services. Citizens' stroke awareness is paramount to guarantee access to treatment, and recent regional campaigns in 2014 [10] and in 2018 (https://salute.regione.emilia-romagna.it/campagne/ ictus-vedo-riconosco-chiamo) might have contributed to early recognition, and encouraged calling emergency services.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although some smaller studies have demonstrated modest benefits, others have shown no or only transient benefits. 51–54 Knowledge of stroke warning signs varies by race, sex, ethnicity, age, education, and urbanicity, 33 which may contribute to disparities in outcomes. Public education campaigns should make every attempt to address underserved groups and those with the largest opportunities to improve awareness.…”
Section: Organization Of Prehospital and Initial Systems Of Carementioning
confidence: 99%
“…In this study, the time of service in the prehospital care was higher for the GTA occurring in the rural area (Soares et al, 2018), justifying such a significant association, since the base of the services that provide prehospital care of the analyzed region is located in the urban zone. In addition, the rural area has different characteristics in relation to the victim's exposure to the event, being conducive to risk behavior by the driver, such as not using protective equipment, driving without a national driver's license, use of alcoholic beverages, and insufficient traffic control in those localities (Denti et al, 2017;Tinoco et al, 2016).…”
Section: Discussionmentioning
confidence: 99%